Role of the autonomic nervous system in osteoarthritis. Issue 5 (October 2017) - Courties, Alice; Sellam, Jérémie; Berenbaum, Francis
Abstract: Joint homeostasis is affected by local and systemic processes. Catecholaminergic and cholinergic fibers innervate the synovium, trabecular bone, and periosteum. Several studies have investigated the involvement of the autonomic nervous system (ANS) in joint homeostasis and the pathophysiology of osteoarthritis (OA). Various resident cells of osteoarticular tissues express receptors for sympathetic and parasympathetic neurotransmitters (norepinephrine/epinephrine and acetylcholine, respectively), which enables them to respond to autonomic stimuli. Furthermore, some of these cells are also able to synthesize neurotransmitters locally and secrete them, which may then act locally regardless of autonomic innervation. The sympathetic nervous system (SNS) is known for promoting bone loss, which has also been demonstrated in the subchondral bone during OA. However, it could interfere with other mechanisms in joint homeostasis. Indeed, intake of beta-blockers decreases pain sensation in individuals with OA; hence, the SNS could be one of the systemic links between hypertension and OA. Parasympathetic fibers may also be implicated in joint homeostasis and local control of inflammation. The vagus nerve has been found to have a strong anti-inflammatory action in other rheumatic diseases through the nicotinic alpha-7 receptor, which is locally expressed by most joint resident cells. Altogether, these data suggest that the ANS is involved in joint homeostasis and OA pathogenesis.